Characterization and development of biosystems and biomaterials - Öchsner, Andreas (Advanced structured materials)
This collection of recent activities provides researchers and scientists with the latest trends in characterization and developments of biosystems and biomaterials. Well known experts present their research in materials for drug delivery, dental implants and filling materials, biocompatible membranes, bioactive surface coatings and bio-compatible and eco-sustainable building materials. In The book covers also topics like microorganisms, the human eye, the musculoskeletal system and human body parts.